Estudio de mercado para la creación de una hostería que mejore la oferta turística en el cantón Bolívar, Manabí - Montesdeoca Chávez, Martha Elizabeth (2022)
The objective of this work is the elaboration of a market study to facilitate the creation of an inn in the Bolivar canton. For this purpose, a methodological process structured in 3 phases was designed; the first phase proposed the baselines to develop the situational tourism diagnosis of the canton, the second phase established the characteristics of the study area, and the third phase determined the analysis of the components of the tourism market. The following results were obtained: in relation to the diagnosis of the canton, it was determined that the population presents socio-community characteristics typical of rural spaces of agricultural and livestock support, it is emphasized that the tourism system of the canton is poorly developed from the supply services, despite this, the territory has a potential of cultural and natural tourism resources and attractions of relevance; The geospatial analysis determined that the Puerto Alto site has ideal geographic characteristics for the creation of an inn since there is no evidence of other similar offers, although there are difficulties in the provision of basic services; Finally, the analysis of the tourism market shows weaknesses in the canton's supply and whose demand emphasizes the expectations of a service that promotes rural, cultural and nature tourism, in order to design recreational activities that enhance the use of the reservoir, this is conclusive that the market study carried out provides assertive guidance for the creation of an inn in the Bolivar canton.